1991
DOI: 10.1289/ehp.94-1567957
|View full text |Cite
|
Sign up to set email alerts
|

A follow-up study of the community near the McColl waste disposal site.

Abstract: To assess the effect of interim clean-up measures on the current health of a community, we conducted a follow-up survey of 193 residents living near the McColl waste disposal site and a comparison area located approximately 5 miles from the site. Results from this survey were compared with results from a similar survey conducted 7 years earlier. Odors were detected at least once per week by 32.7% of "high-exposed" respondents in 1988 compared with 68.5% in 1981, but prevalence odds ratios (PORs) comparing symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(48 citation statements)
references
References 5 publications
1
46
0
1
Order By: Relevance
“…Prevalence odds ratios for specific symptoms in exposed versus unexposed populations were significantly elevated more than 2-fold for 64% of symptoms assessed in one study, with fatigue, headache, poor sleep, nausea, chest pain, and others sometimes showing odds in the 5-to 10-fold range (18). They considered possible mechanisms for increased symptoms to include classical toxicity, an immunological or other physiogenic syndrome, behavioral sensitization, psychosomatic reaction to stress, mass psychogenic illness, reporting bias, confounding factors, or odor, as an effect modifier.…”
Section: Symptoms and The Environmentmentioning
confidence: 92%
See 1 more Smart Citation
“…Prevalence odds ratios for specific symptoms in exposed versus unexposed populations were significantly elevated more than 2-fold for 64% of symptoms assessed in one study, with fatigue, headache, poor sleep, nausea, chest pain, and others sometimes showing odds in the 5-to 10-fold range (18). They considered possible mechanisms for increased symptoms to include classical toxicity, an immunological or other physiogenic syndrome, behavioral sensitization, psychosomatic reaction to stress, mass psychogenic illness, reporting bias, confounding factors, or odor, as an effect modifier.…”
Section: Symptoms and The Environmentmentioning
confidence: 92%
“…Neutra and colleagues considered this in a series of reports that address the higher symptom rates they observed around hazardous waste sites in California (18)(19)(20). Prevalence odds ratios for specific symptoms in exposed versus unexposed populations were significantly elevated more than 2-fold for 64% of symptoms assessed in one study, with fatigue, headache, poor sleep, nausea, chest pain, and others sometimes showing odds in the 5-to 10-fold range (18).…”
Section: Symptoms and The Environmentmentioning
confidence: 99%
“…(32) found increased symptom prevalence only in residents who indicated they were worried about, or aware of, an environmental problem in their neighborhood. The study by Lipscomb et al (18) showed a 2-fold risk in most symptoms for residents who were worried compared to those who were not worried among the exposed population. The authors concluded that being worried, rather than a toxicologic effect from the site, explained the symptoms.…”
Section: Epidemiologic Studies On Health Effects Of Landfill Sitesmentioning
confidence: 98%
“…Very little is known about the likelihood of air exposure from landfill sites through landfill gases or dust. At some of the sites described below, low levels of volatile organic chemicals have been detected in indoor air of homes near landfill sites (7)(8)(9)(10)(11)(12)(13), in outdoor air in areas surrounding sites (14)(15)(16)(17)(18)(19)(20) or in on-site landfill gas (21). Other possible routes of exposure include contamination of soil, ground, and surface water, which may lead to direct contact or pollution of indoor air in the case of evaporation of VOCs into basements of nearby houses.…”
Section: Epidemiologic Studies On Health Effects Of Landfill Sitesmentioning
confidence: 99%
“…En relación con este punto, se ha descrito que las encuestas realizadas en población residente cerca de los sitios de riesgo local reconocido, tienden a mostrar incremento en el autorreporte de resultados y síntomas en salud, como dolor de cabeza, somnolencia, síntomas respiratorios, condiciones sicológicas y problemas gastrointestinales (30)(31)(32)(33). Aunque no es posible descartar un mayor reporte en la población expuesta, otros autores han usado registros médicos que confirman la presencia de algunos síntomas y no muestran la presencia de un reporte aumentado o disminuido (34).…”
Section: Debilidades Y Fortalezasunclassified